TURNOVER INTENTION DITINJAU DARI KOMITMEN, KEPUASAN KERJA DAN KEUNGGULAN BERSAING (STUDI KASUS PADA KARYAWAN PT. SOLO MURNI) - Ferdian Ramadhan Putra; Istiatin Istiatin; Djumali Djumali (ITB AAS INDONESIA Surakarta, 2020)
In addition to reducing the need for workers from other companies, PT also reduces the number of employees. Pure Solo for Boyolali. The aims of this study is to determine the interaction between interactions, To analyze the competitive advantage of job satisfaction and competition goals of PT. Pure Solo for Boyolali. Testing methods include quantitative representation; The sampling technique used in the cluster sample and the Slowan formula provides a sample of 97 employees from the production department. Data analysis techniques used various linear regressions; F test; t test coefficient. The results shown are: 1) Commitment; Job satisfaction and competitive advantage significantly affect the motives and intentions of employees to change PT. Solo Murni, Boyolali, 2) encouraged PT staff to be positive and part of the competition. Purely solo in Boyolali; 3) Job satisfaction has a positive and partial effect on employee motivation to replace PT. According to Boyolali's four competitive advantages, Murni Murni has a positive and partial impact on PT. Staff competition. Pure Solo for Boyolali. Keywords: turnover intention, comitment, job satisfaction, competitive advantage